Կորոնար զարկերակների գնահատումը ստորին վերջույթների զարկերակների օկլուզիոն ախտահարմամբ պացիենտների մոտ - Մանվելյան, Ռ. Լ.; Համբարձումյան, Կ. Մ.; Կոստանյան, Տ. Ս. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Около 42 пациентов с ишемической болезнью сердца страдают заболеваниями периферических артерий, последние наблюдаются у 200 миллионов человек во всем мире. 10 пациентов, включенных в исследование, имеют вышеуказанные заболевания. Пациенты госпитализированы для реваскуляризации периферических артерий. Им выполняли коронароангиографию для оценки необходимости реваскуляризации коронарных артерий. Было принято решение продолжить кардиотерапию вместо коронарной реваскуляризации. При реваскуляризации периферических артерий и в после-операционном периоде у пациентов не развился острый коронарный синдром. В результате реваскуляризации нижние конечности сохранены. About 42% of patients with coronary artery disease suffer from peripheral arterial disease, the latter being observed in 200 million people worldwide. Ten patients included in the study have the above diseases. The patients were hospitalized for revascularisation of peripheral arteries. They underwent coronary angiography to evaluate the need for revascularisation of the coronary arteries. The decision was made to continue cardiotherapy instead of coronary revascularization. During peripheral arterial revascularisation and in the postoperative period, the patients did not develop acute coronary syndrome. As a result of revascularization, the lower extremities were preserved.
Keywords: Բժշկություն